Fluid mechanics in rowing: The case of the flow around the blades - Robert, Y.; Leroyer, A.; Barré, S.; Rongère, F.; Queutey, P.; Visonneau, M. (Procedia Engineering, 2014)
The aim of this research is to develop hydrodynamic models to enhance the knowledge of the propulsion efficiency in rowing. The flow around a rowing blade is a complex phenomenon characterised by an unsteady 3D behaviour, with violent free surface deformation including breakup and with a flexible shaft driven by a 6-DOF movement. The study uses experimental results obtained on an instrumented boat to perform CFD computations. All parameters are considered except the minor role played by the spin rotation of the shaft. The numerical results fit fairly well with experimental data given a high number of uncertainties. Once CFD computations fully validated, more accurate parametric models could be built and integrated in a rowing simulator which will help coaching staff in analysing and improving performance and training of athletes. Another considered possibility is the direct coupling between the rowing simulator and the CFD code.